The position of BRICS towards the Syrian crisis - Hussein, Eslam Ibrahim (Journal of the Belarusian State University. International Relations, 2021)
By the beginning of this century, an international economic grouping called BRICS has emerged, consisting of five countries from the rising powers: Brazil, Russia, India, China and South Africa. There are some attempts and developments within the BRICS grouping aiming to increase the coordination of their stances and foreign policies towards some crises in various regions, especially the crises in the Middle East. Accordingly, this article aims to identify the roles of BRICS as a whole towards the Syrian crisis as one of the most prominent regional crises, and to review and investigate the constants of the positions of BRICS, and to monitor the behaviour and approach of BRICS towards this crisis that represents one of the existing challenges, and to assess the effectiveness of BRICS as some claim that the features of the BRICS grouping as a whole have begun to become clear politically toward the Syrian crisis in particular.